Implementing a work standardization program in XYZ team - Wu, An Ni (Animo Repository, 2018)
This action research aimed to address the work standardization issue of XYZ team in Cushman & Wakefield Inc. on consolidating the different practices of different regions. Currently, the practice gap between each region has been minimized and workflow has been documented property. Collaboration with the team members through formal meetings, casual interviews, email correspondences, and report documents were done in all four steps of action research cycle namely constructing, planning action, taking action and evaluating action. It was found out that there were different understanding in the work process by each database administrator (DBA), different client requests from each region and lack of communication from upper management team and also within the team. Through collaborative efforts, implementation of work standardization program by consolidating the practices of all regions and document the work process and role shifting by each region made a great impact in our team. In doing so, it was sought to build collaborative relationship with the team members to achieve a common goal of providing excellent service quality to our client. This intervention proved to be an effective way to improve the work standardization for the lease administration team for XYZ Company.